Globo H-KLH vaccine adagloxad simolenin (OBI-822)/OBI-821 in patients with metastatic breast cancer: phase II randomized, placebo-controlled study. Issue 2 (22nd July 2020) - Huang, Chiun-Sheng; Yu, Alice L; Tseng, Ling-Ming; Chow, Louis W C; Hou, Ming-Feng; Hurvitz, Sara A; Schwab, Richard B; L Murray, James; Chang, Hsien-Kun; Chang, Hong-Tai; Chen, Shin-Cheh; Kim, Sung-Bae; et al.
Abstract : Purpose: This randomized, double-blind, placebo-controlled, parallel-group, phase II trial assessed the efficacy and safety of adagloxad simolenin (OBI-822; a Globo H epitope covalently linked to keyhole limpet hemocyanin (KLH)) with adjuvant OBI-821 in metastatic breast cancer (MBC). Methods: At 40 sites in Taiwan, USA, Korea, India, and Hong Kong, patients with MBC of any molecular subtype and ≤2 prior progressive disease events with stable/responding disease after the last anticancer regimen were randomized (2:1) to adagloxad simolenin (AS/OBI-821) or placebo, subcutaneously for nine doses with low-dose cyclophosphamide. The primary endpoint was progression-free survival (PFS). Secondary endpoints included overall survival, correlation of clinical outcome with humoral immune response and Globo H expression, and safety. Results: Of 349 patients randomized, 348 received study drug. Patients with the following breast cancer subtypes were included: hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2–) (70.4%), triple negative (12.9%), and HER2+ (16.7%), similarly distributed between treatment arms. Median PFS was 7.6 months (95% CI: 6.5–10.9) with AS/OBI-821 (n=224) and 9.2 months (95% CI: 7.3–11.3) with placebo (n=124) (HR=0.96; 95% CI: 0.74–1.25; p=0.77), with no difference by breast cancer subtype. AS/OBI-821 recipients with anti-Globo H IgG titer ≥1:160 had significantly longer median PFS (11.1 months (95% CI: 9.3–17.6)) versus those with titers <1:160 (5.5 months (95% CI: 3.7–5.6); HR=0.52; p<0.0001) and placebo recipients (HR=0.71; p=0.03). Anti-KLH immune responses were similar at week 40 between AS/OBI-821 recipients with anti-Globo IgG titer ≥1:160 and those with anti-Globo IgG titer <1:160. The most common adverse events with AS/OBI-821 were grade 1 or 2 injection site reactions (56.7%; placebo, 8.9%) and fever (20.1%; placebo, 6.5%). Conclusion: AS/OBI-821 did not improve PFS in patients with previously treated MBC. However, humoral immune response to Globo H correlated with improved PFS in AS/OBI-821 recipients, leading the way to further marker-driven studies. Treatment was well tolerated. NCT01516307.